Composition, distribution and waste management of Playa Grande, the most important touristic beach of Mar del Plata city, Argentina - Denuncio, Pablo Ezequiel (2014)
Beach debris, defined as solid waste materials of anthropogenic origin discarded at sea or reaching the sea through other ways, is one of the most highly visible expressions of human impact on the marine environment. Beaches across the planet accumulate marine debris and this phenomenon has been widely documented on many beaches in different countries (Claereboudt, 2004). Even though beach debris is a worldwide problem, it has been little studied in South America. In Argentina, until the present there have been no intensive studies on distribution, composition and sources of beach debris in touristic beaches from Argentina. Being this crucial a information for urban waste management and beach cleaning purposes, our goal is to evaluate the abundance, sources and distribution of superficial and buried beach debris of Playa Grande, the most important recreational beach of Mar del Plata city, Argentina.